ENHANCEMENT GLUTATHIONE PEROXIDASE ACTIVITY AND Î±2-MACROGLOBULIN GENE EXPRESSION OF MACROBRACHIUM ROSENBERGII FED WITH AQUEOUS MORINDA CITRIFOLIA LEAVES EXTRACT-SUPPLEMENTED DIET - Halim, Atika Marisa; Prajitno, Arief; Chang, Chin Chyuan (University of Muhammadiyah Malang)
Morinda citrifolia, known commercially as noni is often used for enhance immunity, these plant rich of phenolic compound with antioxidant properties. In the present study, Macrobrachium rosenbergii were fed with diets containing of aqueous M. citrifolia leaves extract (AMLE) at 0.6, 4 and 6 g kg-1. Glutathione peroxidase (GPx) activity was conducted to measure immune parameter, these parameter was evaluated before and after 7, 21, 35, 49 and 63 days of feeding trial. Immune gene expression of ?2-macroglubulin (?2-M) was evaluated in this study. The results showed that after 63 days of feeding treatment, significantly increased in GPx activity. Gene expressions of ?2-macroglubulin was significantly upregulated. These results recommend that administration of AMLE can be used as an immunostimulant and regulated immune response and immune gene expression in M. rosenbergii. Keyword: Morinda citrifolia, Macrobrachium rosenbergii, GPx, ?2-M